Marta Requejo Isidro (Ed.). Brussels I Bis. A Commentary on Regulation (EU) No 1215/2012 - Anthimos, Apostolos (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Este artículo reseña: Marta Requejo Isidro (Ed.). Brussels I Bis. A Commentary on Regulation (EU) No 1215/2012. Elgar Commentaries in Private International Law series, 2022, 1024 pp. ISBN: 978 1 78990 816 9